1992
DOI: 10.1103/physrevb.45.11249
|View full text |Cite
|
Sign up to set email alerts
|

Gravity- and strain-induced electric fields outside metal surfaces

Abstract: The gravity-induced electric field outside a metal object supported against gravity is predominantly due to its differential compression which arises in supporting its own weight. This Dessler-Michel-Rorschach-Trammell (DMRT) field, as it has come to be known, is expected to be proportional to the strain derivative of the work function of the surface. We report the results of an experiment designed to produce this effect with mechanically applied strain rather than with gravity. In essence, we have measured th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In section 2 we briefly review our apparatus and technique, which is described in greater detail elsewhere [2,23,24]. We present our results in section 3 and a summary in section 4.…”
mentioning
confidence: 99%
“…In section 2 we briefly review our apparatus and technique, which is described in greater detail elsewhere [2,23,24]. We present our results in section 3 and a summary in section 4.…”
mentioning
confidence: 99%
“…Precision of the Sells in the g tray tribution, is due to the crystal deformation. Recent measurements [21] have shown that the ratio between the gravity-induced electric fields and the weight of antiprotons is close to 1. A measurement of gold electrodes has yielded a ratio less than 0.18.…”
Section: E Stray Charges Effectmentioning
confidence: 96%
“…[the values of the magnetic field and the electric potentials can be properly chosen in order to satisfy (21)]. The effect of the force of gravity is completely negligible at typical experimental conditions for Penning traps (Zp= 1 cm, Vp =a few volts).…”
Section: Cg=mentioning
confidence: 99%
“…In microgravity the limitation of 10 −6 is due to a cyclotron radius of 10 µm; the 10 µm resolution of the detector; and the patch effect. These limitations could be overcome in future experiments by using colder antiprotons, developing higher-resolution detectors and 5 × 10 −13 eV cm −1 DMRT Copper, copper oxides [14] 5 × 10 −14 eV cm −1 DMRT Gold, helium layer [18] 2 × 10 −10 eV cm improving techniques for reducing transverse forces in the trap, including materials with smaller patch fields and higher-order magnetic fields. At this time we see no fundamental limitation to the ultimate precision obtainable in microgravity.…”
Section: Summary Of Sensitivities Expected In Weaxmentioning
confidence: 99%